Development and Validation of the Mindfulness-Based Interventions – Teaching Assessment Criteria (MBI:TAC). (December 2013) - Crane, Rebecca S.; Eames, Catrin; Kuyken, Willem; Hastings, Richard P.; Williams, J. Mark G.; Bartley, Trish; Evans, Alison; Silverton, Sara; Soulsby, Judith G.; Surawy, Christina
Background. The assessment of intervention integrity is essential in psychotherapeutic intervention outcome research and psychotherapist training. There has been little attention given to it in mindfulness-based interventions research, training programs, and practice. Aims. To address this, the Mindfulness-Based Interventions: Teaching Assessment Criteria (MBI:TAC) was developed. This article describes the MBI:TAC and its development and presents initial data on reliability and validity. Method. Sixteen assessors from three centers evaluated teaching integrity of 43 teachers using the MBI:TAC. Results. Internal consistency (α = .94) and interrater reliability (overall intraclass correlation coefficient = .81; range = .60-.81) were high. Face and content validity were established through the MBI:TAC development process. Data on construct validity were acceptable. Conclusions. Initial data indicate that the MBI:TAC is a reliable and valid tool. It can be used in Mindfulness-Based Stress Reduction/Mindfulness-Based Cognitive Therapy outcome evaluation research, training and pragmatic practice settings, and in research to assess the impact of teaching integrity on participant outcome.